Visiting Halal restaurants: the perceptions of non-Muslim postgraduate students in Malaysia's public university - Mohd Shuhaimi, Amarul Arief; Ab Karim, Muhammad Shahrim (Qualitative Research Association of Malaysia, 2021)
The Halal market in Malaysia is unique as it is no longer contributed to and enjoyed solely by the Muslim population but also by non-Muslim citizens. The plethora of Halal-certified food products and restaurants owned by non-Muslims proves that such a market is no longer an exclusive trade. A previous study unveiled that this dietary law is still widely misperceived even in Muslim-majority countries like Malaysia. Numerous studies have been conducted to unravel the perceptions of non-Muslims in Malaysia towards Halal products in various settings and contexts. Nevertheless, such studies are still limited to general populations, with no representation in the educational and academic setting, especially regarding postgraduate students, as others focus on quantitative methods for collecting and analysing data. Hence, this study aims to explore the understanding of non-Muslim postgraduate students in the university setting about the concept of ‘Halal’ and to describe their experiences when visiting Halal restaurants, especially those surrounding the educational setting. The study was conducted at a public higher education institution located in the Klang Valley and was executed using the qualitative method using purposive sampling amongst three non-Muslim postgraduate students, via in-depth interview sessions. Observation of a halal-certified restaurant assisted in triangulating the data. The data was then analysed through the thematic analysis approach by using the Coding, Categorical and Thematic (CoCaT) technique. The results show that some of the postgraduate students had mistakenly viewed Malay food as Halal food while others perceived no significant difference between visiting Halal restaurants and regular restaurants. Future studies are suggested to explore the fundamental ideas and meanings behind the misconceptions towards ‘Halal’ (and Halal restaurants) amongst non-Muslim consumers. This study would be constructive to local entrepreneurs, policymakers, scholars, and media practitioners in spearheading necessary improvements in realigning the misconceptions towards Halal food and restaurants while amplifying local and international markets.